Communism in action : (United States government printing office, 1946)
This book introduce coommunism Soviet union from the revolution to the 5 year plan, the operation of the Soviet productive system, the role of managemt, labor, forced labor, living standards, agriculture, finance, transportation and communication. Soviet political and social.